What Do We Know about Growth Patterns in Pakistan? - López-Cálix, J.R.; Srinivasan, T.G.; Waheed, Muhammad (World Bank, Washington, DC, 2014)
This paper explores stylized facts of Pakistan's growth patterns. It identifies the short-lived predominant character of its increasingly scarce growth accelerations, the average volatility of the growth rate by international standards, the high but decreasing correlation between overall growth and agricultural growth, the long term decline of its growth (potential) rate to around 4.5 percent, well below the 6 percent rate of the 1960s or from the 7 percent rate required for absorbing the young labor force. It also explores the dramatically steady fall in productivity during the 2000s (measured by Total Factor Productivity) and, to a lesser extent, capital accumulation as main reasons of such decline. The paper analyzes the role factor accumulation plays in long-term labor reallocation across sectors, with industry stalling, agriculture still playing a major role that goes beyond its own contribution to GDP, and services playing an increasing role in creating employment, but on low productivity jobs. Growth acceleration is not assured and Pakistan will need to create more jobs moving from agriculture to industry and services in activities where productivity is higher, but to do this, curbing the factors that constraint growth overall and sectoral and Total Factor Productivity in particular will be essential.